Vacuum-assisted mini-ECIRS for calyceal diverticular stones in a recipient of a kidney transplant: A case report - Ponthakorn Srithongsongsaeng; Kun Sirisopana; Surawach Piyawannarat; Yada Phengsalae; Premsant Sangkum; Wisoot Kongchareonsombat; Chinnakhet Ketsuwan (Urology Case Reports)
Urolithiasis in renal allografts can cause serious complications, particularly when involving calyceal diverticula due to altered anatomy. We report the case of a 44-year-old female recipient of a kidney transplant who presented with recurrent urinary tract infections and elevated serum creatinine levels. Imaging revealed a calyceal diverticular stone. After a failed retrograde approach, she underwent vacuum-assisted mini-endoscopic combined intrarenal surgery (ECIRS). A flexible ureteroscope enabled precise puncture and direct visualization for diverticular neck incision and fulguration. The procedure was successful with no complications. Vacuum-assisted mini-ECIRS is a safe and effective option for complex stone cases in recipients of transplants.